Сарматський комплекс із с. Запруддя на Середній Наддніпрянщині - Романюк, Л.М.; Симоненко, О.В. (Археологія, 2001)
В статті розглядається комплекс речей, знайдений 1974 р. під час руйнування кургану біля с. Запруддя Рокитнянського р-ну Київської обл. Аналіз культурної належності та датування дозволяють пов'язати його з сарматами та віднести до І ст. н. е. В 1974 г. при разрушении кургана близ с. Запрудье Рокитнянского р-на Киевской обл. был найден комплекс вещей, включавший в себя два красноглиняных кувшина, краснолаковые арибалл, лагинос и чашку, чернолощеную ойнохою, два серолощеных кувшина, бронзовый котелок, фрагменты серебряного канфара, янтарные, аметистовые, сердоликовые, хрустальные и стеклянные бусы, золотые подвески, бронзовый перстень с геммой, амулеты, обломок терракотовой статуэтки. Аналогии вещам позволили датировать комплекс I в. н. э. и связать его с впускным захоронением (или несколькими синхронными захоронениями) сарматов. In 1974, a complex of things including two red-clay jugs, an aryballos, lagynos, and cup (all are red-lacquered), a red-polished oinochoe, two Grey-polished jugs, a bronze pot, fragments of a silver kanphar, amber, amethyst, carnelian, cut-glass, and glass beads, gold pendants, a bronze ring with gems, amulets, and the fragment of a terra-cotta statuette was found on destroying a barrow near the village of Zapruddya of the Rokutnyans’kyi district of the Kyiv region. The things’ analogs allow us to date the complex to the 1st century AD and to consider it as an intake burial (or several synchronous burials) of the Sarmatians.